Acceptance of Sms Text Information Usage among College Students - Liu, Glory Sze Hui; Guok, Tiong Hock (INTI Publishing House Sdn Bhd, 2005)
Short Message Service (SMS) Text Messaging has become popular as mobile devices increased tremendously in recent years. The modes of communication in modern society have been redefined. Hence, this study was conducted to investigate and explore the usage of SMS text messaging as a notification service for reaching young adult students in a college environment. The questionnaire survey on INTl College students indicated a high acceptance of SMS usage and the preference of notification types or services. A few factors in SMS acceptance among college students were also suggested and discussed. Although confined to SMS text notification in one college, the results were also likely to be relevant to other colleges or tertiary institutions. The writers have also suggested six services that could be incorporated into SMS text notification to enhance the effectiveness and efficiency of communication in a college environment, and to ensure efficient dissemination of information for intended recipients.